Shift in Peaks of PAH‐Associated Health Risks From East Asia to South Asia and Africa in the Future - Sijia Lou; Manish Shrivastava; Aijun Ding; Richard C. Easter; Jerome D. Fast; Philip J. Rasch; Huizhong Shen; Staci L. Massey Simonich; Steven J. Smith; Shu Tao; Alla Zelenyuk (Earth's Future, 2023)
Abstract Lung cancer risk from exposure to ambient polycyclic aromatic hydrocarbons (PAHs) is expected to change significantly by 2050 compared to 2008 due to changes in climate and emissions. Integrating a global atmospheric chemistry model, a lung cancer risk model, and plausible future emissions trajectories of PAHs, we assess how global PAHs and their associated lung cancer risk will likely change in the future. Benzo(a)pyrene (BaP) is used as an indicator of cancer risk from PAH mixtures. From 2008 to 2050, the population‐weighted global average BaP concentrations under all RCPs consistently exceeded the WHO‐recommended limits, primarily attributed to residential biofuel use. Peaks in PAH‐associated incremental lifetime cancer risk shift from East Asia (4 × 10−5) in 2008 to South Asia (mostly India, 2–4 × 10−5) and Africa (1–2 × 10−5) by 2050. In the developing regions of Africa and South Asia, PAH‐associated lung cancer risk increased by 30–64% from 2008 to 2050, due to increasing residential energy demand in households for cooking, heating, and lighting, the continued use of traditional biomass use, increases in agricultural waste burning, and forest fires, accompanied by rapid population growth in these regions. Due to more stringent air quality policies in developed countries, their PAH lung cancer risk substantially decreased by ∼80% from 2008 to 2050. Climate change is likely to have minor effects on PAH lung cancer risk compared to the impact of emissions. Future policies, therefore, need to consider efficient combustion technologies that reduce air pollutant emissions, including incomplete combustion products such as PAH.